Limitations on the right to be forgotten before information of public interest (Research, Society and Development, 2022)
This research intends to analyze the limitations of the right to be forgotten, as a tool to restrain or even hinder the citizen's access to information of public interest. Thus, addressing the right to personality, the right to information, the right to be forgotten, in the civil and procedural sphere. The text discusses past and current situations about the disclosure of facts or truthful data that it was intended to prevent due to the passage of time, thus trying to erase part of the nation's history. Through a deductive methodology, through a doctrinal, legislative and jurisprudential analysis, the text informs the position that Brazilian society establishes for the exercise of the right to be forgotten and what are its limitations. With the objective of promoting the defense of information as a pillar of a nation, since it is through it that history is made, based on the role of the Constitution in publicizing the acts of public agents in the exercise of their functions. The research is part of the project “Constitutional principles and digital law: effects in the civil procedural sphere”, which deals with the social changes that digital and communication media have generated and their valuation in the material and procedural legal environment.